Covidfencing effects on European Cross-Border Regions: an initial outlook - Medeiros, E. (Time to measure impact in border regions: COVID-19 crossing borders, 2020)
• First of all, I would like to thank the organisation for the honourable invitation to speak as a keynote speaker in this very interesting and relevant event. • Indeed, pandemic times have affected in particular cross-border processes and flows. Hence, there is a need to measure its impacts in border regions. • So, when and how can we do this? I would say a valid ex-post impact evaluation normally requires 2 years after the termination of the evaluation subject. So, for assessing the effects provoked by the COVID-19 one would probably need to wait for around 2022, expecting that all goes well. • When it comes to methodologies I can always suggest the use of Target_TIA as a sound, tested, and reliable TIA methodology. When it comes to the analytic dimensions I could suggest analysing the impacts of the covidfencing on the main parameter of the global deterritorialism governance paradigm, in view of a one Europe one System paradigm, since the covidfencing has undermined the normal functioning of cross-border commuting in several cross-border passages, and the economy of cross-border areas. • This map presents some of the policy areas which were mentioned by a CoR Platform e which gives prominence to CB health and CB commuting related covidfencing situations all across Europe, but with particular intensity in the north eastern French border, since this is the area where most of the 2M CB commuters crossing European borders on a daily base. (400.000 of which cross French borders) • But also at the national level, the covidfencing made it clear the need that some countries have for cross-border workers to maintain their public services functioning (namely hospitals). As examples, Luxembourg needed to keep its borders opened for cross-border medical workers coming from France. There was even the proposal to keep them slipping in Luxembourg under certain payment conditions. The same happened for Switzerland and Austria which needs cross-border medical workers from eastern European countries. • So, it was with satisfaction that I saw the creation of the cross-border alliance by MOT+AEBR+CESCI, which realised that similar future pandemic scenarios require a different approach. There is a need to contain the spread of pandemics at their source. This does not necessarily imply the shutdown of national borders. • The following maps finalise my presentation, by showing the EU Interreg-a areas which could beneficiate more from the EU investments in reducing five types of border barriers and thus contributing for a more integrated and deterritorialised EU territory. • Starting with Economic cooperation, we used data from our Polytechnic Milano colleagues which show the CB areas where there is a higher economic capital potential to explore. So it is on the NWE that the economic impacts of covidfencing would be expected to be higher. • In the social CBC domain, a recent study from ESPON identified many existing cases of CB public services, which need to be further explored in basically all EU CB areas, to increase the level of social cooperation. Here the potential impacts of covidfencing are widespread across Europe. • As regards accessibility related barriers, we used our own data, collected in 2017 on the presence and capacity of CB public transports in Europe (Bus and Trains). This shows darker areas which require higher volumes of public investment in improving CB public transports. So, it would be expended that these areas would have higher negative impacts from the covidfencing process. • At the institutional level, it is known that time is key to consolidate CB institutional formal arrangements, and that the NWE together with the Nordic countries have been cooperation in a formal manner since the mid-1950s. So, the remaining CB areas of Europe would probably have higher negative impacts in this institutional domain. • Finally, the cultural domain is supported by data collected for an EC report in which I acted as an adviser, and that identified several Eastern European CB areas (as well as some in Scandinavia and the Iberian Peninsula) still requiring the mitigation of substantial cultural barriers, which are likely to be the most affected by the covidfencing in this cultural domain. These pandemic times have affected, in particular, cross-border processes and flows. Hence, there is a need to measure the covidfencing impacts in border regions. A valid ex-post impact evaluation for assessing the effects provoked by the COVID-19 on cross-border areas would probably need to wait for around 2022. Valid and tested methodologies like TARGET_TIA and the ITEM TIA can be used. Insofar, mid-term impact evaluations are useful to collect crucial data on the main impacts of covidfencing on the main barrier effect dimensions.